A clinical study on the outcomes of tracheostomy in a tertiary care center: a prospective observational study - Venugopal, Devi; Binu Krishnan, Ragitha; Parameswaran, Gopakumar; Kumar M. , Suresh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Tracheostomy is most commonly performed in patients who have difficulty in weaning off a ventilator. This surgical procedure is associated with complications. The present study was aimed to evaluate the outcomes of tracheostomy with primary and secondary objectives. Methods: This study was done in department of ENT, KIMS Health, Trivandrum, Kerala. Based on the inclusion and exclusion criteria 81 patients were included in the study. Study procedure was explained and informed consent was obtained from close relatives or kin of patients. Demographic, clinical and complication data was collected from the patients and analysed with Statistical Package for Social Sciences (20.0 version) software. Correlation was done between complications and period of decanulation. Results: The study was done in 81 patients under gone tracheostomy. Maximum number of patients had age between 61-80 years. Males were more number than females. Portex type of tube used in maximum patients. 70 patients underwent elective and 11 underwent emergency tracheostomy. 74 patients underwent surgery in operation theatre and 5 in an ICU. Prolonged ventilation is the major indication for tracheostomy. Out of 81 patients 55 did not show any complications. 9 patients developed granulations. Significant correlation was observed between complications with period of decanulation. Conclusions: Postoperative care, regular follow up and proper nursing home care is essential for the patients who require prolonged tracheostomy and also to prevent complications with speedy recovery.